A Review of Energy Sector of Bangladesh. (March 2017) - Islam, Saiful; Khan, Md. Ziaur Rahman
Abstract: A brief overview of current electricity generation status and energy scenarios in Bangladesh has been presented in this paper. Being a developing country, the electric energy demand in Bangladesh has been increasing at a significantly high rate. This demand is fuelled by the sustained growth in GDP in recent years. Bangladesh Government has undertaken various projects to meet this rapidly growing demand. New policies have been drafted to cope with the challenges in the energy sector. These policies are also briefly discussed in this paper. The energy pricing issues are also touched. These policies will play a major role in ensuring energy security and in turn sustainable development of the country.